A dynamic model for the planetary bearings in a double planetary gear set. (1st July 2023) - Liu, Jing; Li, Xinbin; Xia, Min
Highlights: A dynamic model for a DPGS including all components is proposed. The proposed model considers the planetary bearing roller and cage dynamics. Effect of the sun gear speed on the contact force and vibrations of planetary bearing is studied. Abstract: Double planetary gear sets (DPGSs) are widely applied to high power and high torque mechanical transmission systems due to the high loading capacity, steady transmission, and high transmission efficiency. Most previous works studied the planetary bearing vibration characteristics without the gear excitations. This work establishes a dynamic model for a DPGS containing all components (sun gear, ring gear, carrier, inner planet, outer planet, planetary bearing roller, and planetary bearing cage). The components' excitations in this work are more comprehensive than the reported references. The proposed model considers the planetary bearing roller and cage dynamics. Moreover, the gear interactions, planetary gear-bearing-carrier interactions, and roller-cage interactions are contained in the proposed model. The vibrations of planetary bearing roller, planet, carrier, and planetary bearing cage are analyzed. The effect of sun gear rotation speed on the planetary bearing contact force, planetary bearing roller-cage impact force, and vibrations of planetary bearing parts are studied. The simulated and experimental results are compared to prove the correctness of proposed model. Moreover, the results from proposed model and model without the cage are compared to show the advantage of proposed model.